Controlling the Growth of the Skin Commensal Staphylococcus epidermidis Using d-Alanine Auxotrophy - David Dodds (American Society for Microbiology, 2020)
ABSTRACT Using live microbes as therapeutic candidates is a strategy that has gained traction across multiple therapeutic areas. In the skin, commensal microorganisms play a crucial role in maintaining skin barrier function, homeostasis, and cutaneous immunity. Alterations of the homeostatic skin microbiome are associated with a number of skin diseases. Here, we present the design of an engineered commensal organism, Staphylococcus epidermidis, for use as a live biotherapeutic product (LBP) candidate for skin diseases. The development of novel bacterial strains whose growth can be controlled without the use of antibiotics or genetic elements conferring antibiotic resistance enables modulation of therapeutic exposure and improves safety. We therefore constructed an auxotrophic strain of S. epidermidis that requires exogenously supplied d-alanine. The S. epidermidis NRRL B-4268 Δalr1 Δalr2 Δdat strain (SEΔΔΔ) contains deletions of three biosynthetic genes: two alanine racemase genes, alr1 and alr2 (SE1674 and SE1079), and the d-alanine aminotransferase gene, dat (SE1423). These three deletions restricted growth in d-alanine-deficient medium, pooled human blood, and skin. In the presence of d-alanine, SEΔΔΔ colonized and increased expression of human β-defensin 2 in cultured human skin models in vitro. SEΔΔΔ showed a low propensity to revert to d-alanine prototrophy and did not form biofilms on plastic in vitro. These studies support the potential safety and utility of SEΔΔΔ as a live biotherapeutic strain whose growth can be controlled by d-alanine. IMPORTANCE The skin microbiome is rich in opportunities for novel therapeutics for skin diseases, and synthetic biology offers the advantage of providing novel functionality or therapeutic benefit to live biotherapeutic products. The development of novel bacterial strains whose growth can be controlled without the use of antibiotics or genetic elements conferring antibiotic resistance enables modulation of therapeutic exposure and improves safety. This study presents the design and in vitro evidence of a skin commensal whose growth can be controlled through d-alanine. The basis of this strain will support future clinical studies of this strain in humans.